Potential of Fermented Eggs For Stunting Prevention: Literature Review - Fadhila, Farah Rosyihana; Nuryanto, Nuryanto; Ayustaningwarno, Fitriyono; Sugiharto, Sugiharto; Rustanti, Ninik; Margawati, Ani (Journal of Applied Food Technology, 2025)
Stunting is a condition of malnutrition that hampers children's physical growth due to inadequate nutritional intake. This condition impacts health, cognitive development, and increases the risk of diseases. The primary causes of stunting include insufficient nutrition, infections, food security, childcare practices, healthcare services, and sanitation. The prevalence of stunting in Indonesia reached 21.6% in 2022. The government has issued Presidential Regulation No. 72 of 2021 to accelerate stunting reduction. To explore the potential of fermented eggs as a nutritional intervention to prevent stunting, this study aims to identify the nutritional benefits of fermented eggs, assess the enhancement of nutrient bioavailability through fermentation, and evaluate the effectiveness of fermented eggs in improving children's nutritional status. This literature review gathers and analyses studies related to the nutritional impact of fermented eggs. Fermentation enhances the digestibility and bioavailability of proteins, fats, and micronutrients such as B vitamins, folate, and iron. This process breaks down complex proteins and fats into simpler, more absorbable forms. Fermented eggs present a potential solution for preventing stunting by improving digestibility and nutrient bioavailability while providing beneficial probiotics that support overall health. Given their nutritional profile, fermented eggs can serve as an effective and sustainable nutritional intervention.